HELA: national picture 2001 - UK. Health and Safety Commission (Sudbury, 2001)
"The National Picture continues the annual series of LA (Local Authorities ) health and safety statistics. It presents a picture of LA work in enforcing health and safety law, includes indicators of LA enforcement and gives an overview of workplace injuries reported to LAs."